The Influence of Social Media Marketing and Product Diversity on Honda Motorcycle Purchase Interest at PT. Berlian Bintang Mas - Prycillia Putri Dwi Vani; Dian Setyorini; Hommy Dorthy Ellyany Sinaga; Edwin Sugesti Nasution; Fery Wahyudi (LP2M IAIN Palopo, 2026)
This study aims to determine the simultaneous and partial influence of social media marketing and product diversity on purchase intention at PT. Berlian Bintang Mas. Data were obtained from 110 respondents, customers of PT. Berlian Bintang Mas, using purposive sampling. Data analysis used multiple linear regression with the model: purchase intention = 1.678 + 0.268 social media marketing + 0.449 product diversity + e. The results indicate that partially, social media marketing and product diversity have a positive and significant influence on purchase intention, as evidenced by a significance value below 0.05 and a calculated t-test greater than the t-table, as evidenced by an F-value of 1647.489 with a significance below 0.05. The coefficient of determination (R²) of 0.969 indicates that 96.9% of the variation in purchase intention can be explained by social media marketing and product diversity, while the remaining 3.1% is influenced by other factors outside this research model.